Images of Trebizond and the Pontos in Contemporary Literature in English with a Gothic Conclusion - Dąbrowska, Małgorzata (Text Matters: A Journal of Literature, Theory and Culture, 2016)
A Byzantinist specializing in the history of the Empire of Trebizond (1204–1461), the author presents four books of different genres written in English and devoted to the medieval state on the south coast of the Black Sea. The most spectacular of them is a novel by Rose Macaulay, Towers of Trebizond. Dąbrowska wonders whether it is adequate to the Trebizondian past or whether it is a projection of the writer. She compares Macaulay’s novel with William Butler Yeats’s poems on Byzantium which excited the imagination of readers but were not meant to draw their attention to the Byzantine past. This is, obviously, the privilege of literature. As a historian, Dąbrowska juxtaposes Macaulay’s narration with the historical novel by Nicolas J. Holmes, the travelogue written by Michael Pereira and the reports of the last British Consul in Trabzon, Vorley Harris. The author of the article draws the reader’s attention to the history of a rather unknown and exotic region. The Empire of Trebizond ceased to exist in 1461, conquered by Mehmed II. At the same time the Sultan’s army attacked Wallachia and got a bitter lesson from its ruler Vlad Dracula. But this Romanian hero is remembered not because of his prowess on the battlefield but due to his cruelty which dominated literary fiction and separated historical facts from narrative reality. The contemporary reader is impressed by the image of a dreadful vampire, Dracula. The same goes for Byzantium perceived through the magic stanzas by Yeats, who never visited Istanbul. Rose Macaulay went to Trabzon but her vision of Trebizond is very close to Yeats’s images of Byzantium. In her story imagination is stronger than historical reality and it is imagination that seduces the reader.